THE PERFORMANCE OF NURSES AND ARTIFICIAL INTELLIGENCE IN DIRECT CARE ASSISTANCE: PREVENTION AND CARE WITH PIs TO THE PATIENT IN INTENSIVE CARE - Fonseca, Maximiana Aparecida dos Reis (2023)
Objective: to identify the functions of the Nurse in the Intensive Care Unit and the functions of Artificial Intelligence (ChatGPT3) in the face of direct care for patients in intensive care for the prevention and care of PIs. Methodology: the foundation of the research was based on integrative literature research and the collision of the data with the Artificial Intelligence ChatGPT3 from OpenAI.com in a quantitative and qualitative way with the selected data. Results: The performance data of professional nurses in the intensive care unit for coping with artificial intelligence showed, at certain points, signs of reflection and concerns about the arrival of artificial intelligence. Conclusion: The role of the nurse in a scenario with Artificial Intelligence as a partner will require adaptation from the nurse, since, being a machine, it presents high levels of effectiveness and performance, even simulating human action in many processes to a high degree. . Keywords: Artificial Intelligence, Nurse, ChatGPT3